Large scale distribution of ultra high energy cosmic rays detected at the Pierre Auger Observatory with zenith angles up to 80° - Dova, María Teresa (2015)
We present the results of an analysis of the large angular scale distribution of the arrival directions of cosmic rays with energy above 4 EeV detected at the Pierre Auger Observatory including for the first time events with zenith angle between 60° and 80°. We perform two Rayleigh analyses, one in the right ascension and one in the azimuth angle distributions, that are sensitive to modulations in right ascension and declination, respectively. The largest departure from isotropy appears in the E > 8 EeV energy bin, with an amplitude for the first harmonic in right ascension r1a = (4.4 ± 1.0) ´ 10- 2, that has a chance probability P(⩾ra) = 6.4 ´ 10- 1 5, reinforcing the hint previously reported with vertical events alone.